Diversity and local status of bryophytes in Mai pokhari of Ilam district, east Nepal - Pradhan, Nirmala; Heimstad, Ragnhild (Journal of Natural History Museum, 2018)
Bryophytes in Mai Pokhari area of Ilam District, east Nepal was studied in September 2013 to investigate species diversity and status. A total of 42 bryophytes were compiled occurrence status. Plagiochila exigua (Taylor) Taylor, Dicranella setifera (Mitt.) A. Jaeger, Trematodonkurzii Hampe ex Gangulee and Pseudobarbella niitakayamensis Nog. recorded in this study are new additions to Nepal. Wet and damp areas around this lake are suitable habitats for thesporophytic growth of man+y bryophyte species.